Exosomal cargo-loading and synthetic exosomemimics as potential therapeutic tools - LI Song-pei; LIN Zhong-xiao; JIANG Xue-yan; YU Xi-yong (Acta Pharmacologica Sinica, 2018)
Abstract Exosomes are nano-sized vesicles that serve as mediators for intercellular communication through the delivery of cargo, including protein, lipids, nucleic acids or other cellular components, to neighboring or distant cells. Exosomal cargo may vary in response to different physiological or pathological conditions. The endosomal sorting complex required for transport (ESCRT) family has been widely accepted as a key mechanism in biogenesis and cargo sorting. On the other hand, accumulating evidence show that ESCRTindependent pathways exist. Due to the critical role of exosomes in intercellular communications in delivering cargo to recipient cells, exosomes have been investigated as a vector for the delivery of endogenous or exogenous cargo for therapeutic purposes. But the number of exosomes produced by cells is limited, which hampers their application. Synthetic exosome-mimics have been fabricated and investigated as a therapeutic tool for drug delivery. This review focuses on ESCRT-independent regulation of cargo loading into exosomes, including lipid raft and ceramide-mediated mechanisms, and reported exosomes or exosome-mimics with therapeutic effects.